TAZ integrates ECM remodeling with uterine stromal differentiation to maintain early pregnancy - Xueting He; Shizu Aikawa; Yamato Fukui; Chihiro Ishizawa; Ryoko Shimizu-Hirota; Daiki Hiratsuka; Takehiro Hiraoka; Mitsunori Matsuo; Yasushi Hirota (Proceedings of the National Academy of Sciences, 2026)
The uterine microenvironment is critical for establishing pregnancy and sustaining embryonic development. Embryo attachment induces profound endometrial transformation, including stromal differentiation and vascularization, termed decidualization. This process, conserved in humans and rodents, supports the embryo even before placentation. Poorly formed decidua leads to fetal growth restriction or placental defects, yet underlying mechanisms remain unclear. Here, we used single-cell RNA-seq of mouse and human endometria, including patient samples, to uncover key regulators. We identified that collagen-related extracellular matrix (ECM) remodeling depends on TAZ, a central effector of Hippo signaling, and is essential for decidual formation. ECM pathways were enriched in differentiating stromal cells alongside upregulation of TAZ and associated transcription factors. Conditional uterine knockout of TAZ ( Wwtr1 flox/flox Pgr Cre/+ ; Wwtr1 -uKO) caused pregnancy failure in mice, marked by defective trophoblast invasion, early embryonic degradation, and severe subfertility. Spatial transcriptomic and histological analyses of TAZ-deficient endometria further revealed impaired decidualization, ECM remodeling, and vascularization. Thus, TAZ promotes temporal ECM remodeling at the feto–maternal interface, ensuring functional decidual zone formation and healthy pregnancy outcomes.